Molecular dependencies and genomic consequences of a global DNA damage tolerance defect - Daniel de Groot; Aldo Spanjaard; Ronak Shah; Maaike Kreft; Ben Morris; Cor Lieftink; Joyce J. I. Catsman; Shirley Ormel; Matilda Ayidah; Bas Pilzecker; Olimpia Alessandra Buoninfante; Paul C. M. van den Berk; et al. (Genome Biology)
Abstract Background DNA damage tolerance (DDT) enables replication to continue in the presence of fork stalling lesions. In mammalian cells, DDT is regulated by two independent pathways, controlled by the polymerase REV1 and ubiquitinated PCNA, respectively. Results To determine the molecular and genomic impact of a global DDT defect, we studied PcnaK164R/−;Rev1−/− compound mutants in mouse cells. Double-mutant cells display increased replication stress, hypersensitivity to genotoxic agents, replication speed, and repriming. A whole-genome CRISPR-Cas9 screen revealed a strict reliance of double-mutant cells on the CST complex, where CST promotes fork stability. Whole-genome sequencing indicated that this double-mutant DDT defect favors the generation of large, replication-stress inducible deletions of 0.4–4.0 kbp, defined as type 3 deletions. Junction break sites of these deletions reveal microhomology preferences of 1–2 base pairs, differing from the smaller type 1 and type 2 deletions. These differential characteristics suggest the existence of molecularly distinct deletion pathways. Type 3 deletions are abundant in human tumors, can dominate the deletion landscape, and are associated with DNA damage response status and treatment modality. Conclusions Our data highlight the essential contribution of the DDT system to genome maintenance and type 3 deletions as mutational signature of replication stress. The unique characteristics of type 3 deletions implicate the existence of a novel deletion pathway in mice and humans that is counteracted by DDT. Graphical Abstract